Linking Reinforcement Strategies to Employee Performance: Evidence from an Indonesian HRM Case Study - Nadaruddin Nadaruddin; Nisma Iriani; Arjang Arjang (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2025)
This study investigates the influence of incentive, reward, and punishment mechanisms on employee performance within the context of PT. Ecotropika Multikonsultan, a leading environmental consultancy firm in Indonesia. Drawing on reinforcement theory and strategic human resource management frameworks, the research aims to evaluate the effectiveness of both positive and corrective motivational tools in enhancing workplace outcomes. The study employs a quantitative survey approach, utilizing structured questionnaires distributed to 64 employees, followed by multiple linear regression analysis to assess variable influence. The findings indicate that all three factors—rewards, incentives, and punishment—have a significant and positive impact on employee performance, with reward exerting the strongest influence. These results underscore the importance of integrating both motivational and disciplinary strategies within HRM to drive performance. The study contributes to the literature by offering empirical insights into the nuanced application of behavioral reinforcement in a real-world organizational setting. While the scope is limited to a single institution, the implications are broadly relevant for organizations aiming to foster performance-driven cultures. This research provides actionable guidance for HR professionals and organizational leaders on how to optimize workforce potential through strategically designed incentive and control systems.